Taste and the TV chef : how storytelling can save the planet - Smith, Gilly (Intellect Books, 2020)
Examines the evolution of food-centric TV; how it changed Britain's relationship with food and created a global appetite for culinary content. Includes rare interviews with editors and producers who created some of the most influential stories television ever told. Discusses influence of chefs incl. Jamie Oliver, Nigella Lawson and Gordon Ramsay.